Styles of business communication in the context of micro and macro social environment - Tolochek, Vladimir A.; Belik, Veronika V.; Panov, Andrey U. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
Authors analyze the content of typical styles of business communication (SBC) of managers (41 pers.) in commercial company. Identified and described six types of styles of business communication, five are unconstructive («Cooperation, assistance, support, flexibility and compromise»; «Avoiding of business interactions, distant»; «Authoritarian, aggressive, demanding»; «Spontaneous, emotionally uncontrolled communication»; «Formal, distant communication»; «Emotional relationship with the unconstructive business interactions»). The research shows that the determinants of the styles of business communication are the conditions of social micro-environment (family and working groups) and the mesoenvironment – declared and latent features of corporate culture, enshrined in the tradition of building relationships, broadcasting leaders typical company management style, supported by veterans in organization. The second group is socio-demographic, professional job characteristics and temporal characteristics of professional career (total length of work, length of work in the organization, work experience in position).
Keywords: styles; business communication; managers; social environment determinants; temporal characteristics; professional career